The Influence of Performance-Contingent Rewards on Proactive and Responsive Creativity: Dual-Path Mediating Effects of Work Motivation - Li, Chunling; Jiang, Xinqing; He, Hui; Zhang, Xiying (Frontiers in Psychology, 2022)
Creativity has become prevalent in the routine work of knowledge employees in contemporary enterprises. Based on the ambidexterity and self-determination theory, the present study highlights the driver behind proactive and responsive creativity. Using two-stage longitudinal data collected from 373 knowledge employee-supervisor dyads in information and manufacturing companies in China, this study shows that autonomous and controlled motivation play a dual-path mediating mechanism in the effects of pay for performance (PFP) on proactive and responsive creativity. Specially, first, PFP has an inverted U-shaped influence on autonomous motivation, and then autonomous motivation has a positive influence on proactive creativity, ultimately resulting in an inverted U-shaped influence of PFP on proactive creativity. Second, PFP has an inverted U-shaped influence on controlled motivation, and then controlled motivation has a negative influence on responsive creativity, ultimately resulting in has a U-shaped of PFP influence on responsive creativity. Managers should enhance the ambidextrous ability to deal with proactive and responsive creativity and establish an applied and dynamic PFP policy of intensity to drive ambidextrous creativity.